Retinal ischemia due to extramedullary plasmacytomas of the orbit. (February 2020) - Lasocki, Arian; Furphy, Emma-Jane; Westerman, David A.; Harrison, Simon
Highlights: Visual disturbance is a common complaint in patients with multiple myeloma. The differential is broad, as any ocular structure may be affected. Orbital plasmacytomas can cause retinal ischaemia due to mass effect. Orbital plasmacytomas can occur at any stage in the course of the disease. Underappreciation of this entity may result in a delay in diagnosis. Abstract: Visual disturbance is a common complaint in patients with multiple myeloma, both at diagnosis and later in their course, and has a broad differential. Here, we report a novel cause of visual disturbance, namely retinal ischemia due to extramedullary plasmacytomas of the orbit. A 69 year-old male patient with known multiple myeloma presented with reduced vision in his left eye. The patient had been initially diagnosed with IgG myeloma 9 months earlier and multiples lines of medical therapy had been unsuccessful. Ophthalmology review was organised and fundoscopic examination showed evidence of retinal ischemia. Computed tomography of the orbits demonstrated multiple enhancing masses within both orbits, consistent with extramedullary plasmacytomas. The presence of retinal ischemia was thus attributed to mass effect on the orbital vessels. Extramedullary plasmacytomas within the orbit are a rare manifestation of multiple myeloma, but important to consider as a possible cause of visual disturbance.